2015
DOI: 10.1371/journal.pone.0132425
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities along the Prevention of Mother-to-Child Transmission Services Cascade in South Africa: Uptake, Determinants, and Attributable Risk (the SAPMTCTE)

Abstract: ObjectivesWe examined uptake of prevention of mother-to-child HIV transmission (PMTCT) services, predictors of missed opportunities, and infant HIV transmission attributable to missed opportunities along the PMTCT cascade across South Africa.MethodsA cross-sectional survey was conducted among 4–8 week old infants receiving first immunisations in 580 nationally representative public health facilities in 2010. This included maternal interviews and testing infants’ dried blood spots for HIV. A weighted analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
83
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 17 publications
7
83
4
Order By: Relevance
“…We also found moderately high rates of harmful alcohol use during pregnancy, with the youngest women (18–21) reporting the highest rates of risky alcohol use (29%) and alcohol-related harm (37%). Depressive symptoms and risky alcohol use may be contributing to and be consistent with emerging literature regarding poor PMTCT engagement and outcomes among younger HIV-infected pregnant women (Ramraj 2015; Ronen 2015; Woldesenbet et al 2015). …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We also found moderately high rates of harmful alcohol use during pregnancy, with the youngest women (18–21) reporting the highest rates of risky alcohol use (29%) and alcohol-related harm (37%). Depressive symptoms and risky alcohol use may be contributing to and be consistent with emerging literature regarding poor PMTCT engagement and outcomes among younger HIV-infected pregnant women (Ramraj 2015; Ronen 2015; Woldesenbet et al 2015). …”
Section: Discussionsupporting
confidence: 79%
“…Young women in South Africa are also at high risk of new HIV acquisition, with the highest lifetime risk occurring before the age of 25 (Kharsany et al 2012; Pettifor et al 2005). Emerging data from Kenya and South Africa demonstrated that being an HIV-infected adolescent mother was associated with decreased engagement in antenatal care, lower uptake of prevention of mother-to-child transmission (PMTCT) services and antiretroviral therapy (ART), increased dropout at all stages of the PMTCT care and treatment cascade, and 2–3 times the odds of mother-to-child HIV transmission when compared to adult women (Fatti et al 2014; Horwood et al 2013; Ramraj 2015; Ronen 2015; Woldesenbet et al 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a reduction in percentage MTCT, the number of infant HIV infections per 100 000 live births at six weeks postpartum, was above the global validation target. Eliminating unidentified maternal HIV infections [23,24], reducing maternal HIV prevalence and improving retention in HIV-related care (early cART initiation and adherence) [25] are critical to closing current gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Drop-out from the PMTCT cascade has been associated with lack of on-site HIV testing, delayed HIV testing results, lack of HIV serostatus awareness, nondisclosure to partners and delayed ART initiation (Woldesenbet et al, 2015). These barriers to PMTCT highlight the need to identify challenges and devise solutions to enhance PMTCT protocol implementation in rural South Africa.…”
mentioning
confidence: 99%